ANALISIS EFISIENSI EKONOMI PENGGUNAAN FAKTOR-FAKTOR PRODUKSI PADA USAHATANI PAPRIKA DI DESA TLOGOSARI KECAMATAN TUTUR KABUPATEN PASURUAN - Putri Dewi Setianingsih; Mashuri Machfudz; Zainul Arifin (Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2020)
Paprika plants are widely developed in Tutur District, Pasuruan Regency, East Java. Production of whether paprika farming provides benefits, so research is needed to find out the factors of production that affect the production of paprika in Tlogosari Village, Tutur District and To find out the optimal allocation. Paprika production factor use in Tlogosari Village, Tutur District. This research method is a quantitative method with a purposive sampling of locations and respondents as many as 33 people with samples taken by random sampling. The results of this study indicate that 1) Production factors that significantly affect the number of plants and Abemix A&B fertilizer. 2) The number of plants has not been economically efficient so that the addition is needed to be optimal, while the use of Abemix A&B fertilizers is not economically efficient so it should be reduced to be optimal.